Kinematics of the elbow and stifle joints in greyhounds during treadmill trotting An investigation of familiarisation - Owen, M. R.; Richards, J.; Clements, D. N.; Drew, S. T.; Bennett, D.; Carmichael, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
We studied the familiarisation time required to obtain reliable sagittal plane kinematics for the elbow and stifle joints in eleven treadmill-naïve greyhounds trotting on a treadmill. Motion analysis software was used to measure sagittal elbow and stifle joint movements and to calculate joint angular velocities. After a twominute walking initiation period, the dogs trotted for two and a half minutes. Three trials of three seconds (27 to 30, 72 to 75 and 117 to 120 seconds) trotting, each comprising four complete strides, were analysed. The angle versus time and angular velocity versus time graphs were plotted. For each stride, angular velocity and angular velocity data at key points during the gait cycle were recorded. These angles corresponded with the flexion and extension angles and the peak angular velocities of the elbow and stifle joints during stance and swing phase. Reliable elbow and stifle joint kinematics were obtained within 30 seconds of trotting, which did not differ significantly over the twominute test period indicating that the dogs had familiarised to the treadmill.
Keywords: Kinematics; treadmill; gait analysis; greyhound